Citric Acid-catalyzed Solvent Free, an Efficient One-pot Synthesis of 2, 3-Dihydro-1H-1, 5-Benzodiazepine Derivatives - khan, Mohammad A. Baseer1 and Asgar Jafar (Recent Research in Science and Technology, 2011)
2,3-Dihydro-1H-1,5-benzodiazepines are synthesized by reaction of o-Phenylenediamine with ketones (acyclic / cyclic) under solvent free conditions in the presence of citric acid in short reaction time with excellent yield.